Perspective of Punishment Goals for Narcotics Addicts in Health Aspect of Medical Rehabilitation - Gusti Ayu Utami; Andi Ervin Novara Jaya (Science Techno Health Journal, 2024)
Drug addiction has long been a serious problem in various countries. This is also exacerbated by the development of technology that is utilized by criminals in launching their actions including in the criminal act of drug trafficking which has an impact on the number of drug abusers in Indonesia. Drug users or addicts can essentially be said to be sick people so it is very unwise if in the implementation of the punishment to mix sick people (drug addicts) with other criminal offenders. The regulations in Law No.35 of 2009 concerning Narcotics contain several interpretations in the implementation of law enforcement, especially for narcotics abusers and narcotics addicts, where most of the law enforcement efforts in i tend to bring them into the judicial area, the implementation of rehabilitation carried out still raises many obstacles which result in efforts to fulfill the rights of narcotics users not being maximized. However, in fact, the regulations used as the basis for providing rehabilitation still have shortcomings both in terms of substance and in terms of implementation by law enforcers and related institutions appointed by the government. This causes the main purpose of imposing rehabilitation not to be properly achieved as one of the objectives of punishment. The research method used is normative juridical. The process of making this journal plays an important role in determining the rehabilitation of narcotics addicts. The formulation of the problem to be discussed, namely: 1) How is the legal review of narcotics addicts in the perspective of the purpose of punishment, 2) How are medical rehabilitation efforts against narcotics addicts.